2022
DOI: 10.12703/r/11-19
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the management of transient ischemic attacks

Abstract: Transient ischemic attack (TIA) constitutes an important clinical condition, indicating the presence of considerable risk for a subsequent ischemic stroke. Its prompt diagnosis and management have the potential for reducing the risk of neurologic disability, highlighting the critical need to prioritize the care of patients with TIA. The risk of ischemic stroke following a TIA is directly related to its etiopathogenesis, and recognizable causes are commonly categorized within one of three domains: cerebrovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 176 publications
0
2
0
Order By: Relevance
“…Ischemic stroke is caused by interruption of cerebral blood flow due to an obstruction and the main risk factors for ischemic, hemorrhagic and transient stroke are due to the sedentary lifestyle that generates overweight, the chronic consumption of alcohol or narcotics (cocaine, methamphetamines). Pathologies that favor the occurrence of transient ischemic, ischemic or hemorrhagic accidents are represented by heart diseases (heart failure, congenital heart malformations, heart infections, heart rhythm disorders), obstructive sleep apnea syndrome [ 83 ]. Recent studies showed the involvement of TRPM2 in pathogenesis factors of ischemic stroke as follows: by reducing oxidative stress in cardiomyocytes, TRPM2 reduces inflammation and stimulates the remodeling of the atria; it models endothelial dysfunction by deregulating the influx of calcium ions, mediates the damaging effects of ROS on the endothelium and favors hypertension; induces the death of pancreatic β cells that secrete insulin, thus promoting the development of diabetes; promotes the aggregation of platelets and favors the appearance of vascular thrombus [ 84 86 ].…”
Section: Trpm2 In Ischemic Reperfusion Injurymentioning
confidence: 99%
“…Ischemic stroke is caused by interruption of cerebral blood flow due to an obstruction and the main risk factors for ischemic, hemorrhagic and transient stroke are due to the sedentary lifestyle that generates overweight, the chronic consumption of alcohol or narcotics (cocaine, methamphetamines). Pathologies that favor the occurrence of transient ischemic, ischemic or hemorrhagic accidents are represented by heart diseases (heart failure, congenital heart malformations, heart infections, heart rhythm disorders), obstructive sleep apnea syndrome [ 83 ]. Recent studies showed the involvement of TRPM2 in pathogenesis factors of ischemic stroke as follows: by reducing oxidative stress in cardiomyocytes, TRPM2 reduces inflammation and stimulates the remodeling of the atria; it models endothelial dysfunction by deregulating the influx of calcium ions, mediates the damaging effects of ROS on the endothelium and favors hypertension; induces the death of pancreatic β cells that secrete insulin, thus promoting the development of diabetes; promotes the aggregation of platelets and favors the appearance of vascular thrombus [ 84 86 ].…”
Section: Trpm2 In Ischemic Reperfusion Injurymentioning
confidence: 99%
“…Twenty years later, the NIH defined TIA as temporary focal neurologic deficit of vascular origin, with a rapid onset (between one to five minutes), lasting as long as 24 h. This time frame definition evolved to transient neurologic deficits caused by focal brain, spinal cord or retinal ischemia without acute infarction, and without imaging evidence of infarction, thus, the key modern TIA definition is a tissue-based versus a time-frame diagnosis. In general, the main difficulty clinicians encounter is delayed presentation after symptom resolution [ 1 ].…”
Section: The Diagnostic Challenge Of a Transient Ischemic Attack Pres...mentioning
confidence: 99%